Transitioning from Conventional to Organic Farming Using Conservation Tillage - D. L. Wright; J. Moyer; D. Treadwell; I. M. Small; S. George (EDIS)
Organic farming is one of the fastest-growing segments of the agricultural industry in the United States and in Florida. Conservation tillage is often employed to reduce soil erosion, improve physical and biological properties of soil, and increase water use efficiency. This 5-page article aims to provide recommendations to row crop farmers who wish to implement conservation tillage practices during their transition to a certified organic system. Written by D. L. Wright, J. Moyer, D. Treadwell, I. M. Small, and S. George, and published by the UF/IFAS Agronomy Department, revised November 2020.